2017
DOI: 10.1093/mnras/stx2355
|View full text |Cite
|
Sign up to set email alerts
|

Binary stars in the Galactic thick disc

Abstract: The combination of asteroseismologically-measured masses with abundances from detailed analyses of stellar atmospheres challenges our fundamental knowledge of stars and our ability to model them. Ancient red-giant stars in the Galactic thick disc are proving to be most troublesome in this regard. They are older than 5 Gyr, a lifetime corresponding to an initial stellar mass of about 1.2 M . So why do the masses of a sizeable fraction of thick-disc stars exceed 1.3 M , with some as massive as 2.3 M ? We answer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 91 publications
6
98
0
Order By: Relevance
“…For the latter sample, we selected stars with Galactic periapses 6.6 kpc > and apoapses 10.0 kpc < in order to produce a sample with similar kinematics to KELT-21. For both samples, we excluded stars with [C/N]>−0.4 in order to exclude stars that are likely merger products or have experienced significant mass gain due to binary interactions, and are therefore likely older than would be assumed given their other properties (cf., Izzard et al 2018 Figure 13. It is apparent that KELT-21ʼs Fe H [ ] is at the lower end of these distributions, but it is not a dramatic outlier.…”
Section: Metal Content and Galactic Contextmentioning
confidence: 99%
“…For the latter sample, we selected stars with Galactic periapses 6.6 kpc > and apoapses 10.0 kpc < in order to produce a sample with similar kinematics to KELT-21. For both samples, we excluded stars with [C/N]>−0.4 in order to exclude stars that are likely merger products or have experienced significant mass gain due to binary interactions, and are therefore likely older than would be assumed given their other properties (cf., Izzard et al 2018 Figure 13. It is apparent that KELT-21ʼs Fe H [ ] is at the lower end of these distributions, but it is not a dramatic outlier.…”
Section: Metal Content and Galactic Contextmentioning
confidence: 99%
“…Furthermore, Tayar et al (2015) found that one of these stars was rapidly rotating, another sign that an interaction could be involved. Together with the theoretical work by Izzard et al (2018) there is mounting evidence that at least a significant part of the massive, i.e. young α-rich stars is a result of binary interactions.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions can either produce a higher mass star in a binary through mass transfer, or a more massive single star through a merger. However, one needs to note that the main conclusions of Izzard et al (2018) are a prediction that the fraction of thick disk giants with mass in excess of 1.3 M ⊙ ranges from 0.8 to 3 percent in all but one of their model sets. In contrast, Martig et al (2015) found ∼6% of their α-rich stars were high mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above discussions have considered the evolution of single stars. In a recent paper, Izzard et al (2018) discuss mass-transfer and stellar mergers, in the context of explaining the presence of fairly massive stars in the old population of the Galactic thick disk. They raise the possibility that C-poor and N-rich stars could be the result of binary-star interactions that expose CN-processed material at the surface, such as in the CDRGs.…”
Section: Evolutionary Statusmentioning
confidence: 99%